Peran Agroteknologi dalam Meningkatkan Produktivitas Pertanian - Warnia Zai; Yuwan Martin Ziliwu; Pikirkan Waruwu (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Agrotechnology plays a crucial role in increasing agricultural productivity through the implementation of modern innovations and technologies. Challenges such as land degradation, climate change, and limited natural resources can be addressed through precision technology, smart irrigation, biotechnology, and agricultural mechanization. This study employs a literature review method by analyzing various studies from 2019 to 2024 that discuss the impact of agrotechnology on agricultural yields. The findings indicate that the application of precision irrigation systems can enhance water use efficiency by up to 40%, while the use of genetically engineered superior crop varieties can increase yields and improve plant resistance to pests and diseases. Additionally, the utilization of digital technology, such as the Internet of Things (IoT), enables more efficient and data-driven land management. However, major challenges in implementing these technologies include limited farmer access, high investment costs, and low digital literacy among farmers. Therefore, policy support, financial incentives, and farmer training are necessary to ensure the widespread and sustainable adoption of technology. Thus, agrotechnology can serve as a primary solution for increasing agricultural productivity while maintaining environmental sustainability.